The Influence of Promotion and Service Quality on BPJS Patient Satisfaction at Clinic "X" - Putri, Aulia; Nur Manah, Siti; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (International Journal of Business, Law, and Education, 2025)
First-Level Health Facilities (Fasilitas Kesehatan Tingkat Pertama/FKTP) play a critical role in delivering healthcare services to participants of the National Health Insurance (BPJS) program in Indonesia. Every BPJS participant has the right to select an FKTP that collaborates with BPJS Health based on their preference. Therefore, FKTPs, including clinics partnering with BPJS Health, must actively promote their services and continuously enhance the quality of care to improve patient satisfaction and attract more BPJS participants. This study employs a quantitative, causal approach to examine the influence of promotion and service quality on BPJS patient satisfaction. Using a cross-sectional design and random sampling technique, data were collected through questionnaires from 63 BPJS patients at clinic "X." The data were analyzed using descriptive analysis and multiple linear regression, resulting in the regression equation Y = 1.245 + 0.077 X1 + 0.844 X2. The findings indicate that promotion and service quality significantly influence BPJS patient satisfaction, both individually and jointly, at clinic "X." These results highlight the importance of strategic promotion and continuous quality improvement by FKTPs to ensure optimal healthcare delivery and patient satisfaction among BPJS participants.